A Typology Linguistic Study: Is the Sibolga Coastal Dialect Ergative? - Rezeki, Tri Indah; Mulyadi (Journal of Language Development and Linguistics, 2024)
This research explores the existence of ergative language features in the Sibolga Coastal dialect. Qualitative descriptive methods were used to analyze data obtained from nine folktale titles in Bunga Rampai Rakyat Tapanuli Tengah (The anthology of central Tapanuli folktales). Of the nine stories, ten clauses were found to show an ergative pattern, where the subject in the first clause acts as the object in the second clause. The findings show that the Sibolga Coastal dialect language has the characteristics of an ergative language in its structure, with a pattern where the subject of the first clause becomes the object of the following clause. These findings indicate a tendency to use ergative language features in the Sibolga Coastal dialect. This research concludes that the Sibolga Coastal dialect uses ergative language features, although in limited quantities. These findings contribute to understanding the syntactic structure of the Sibolga Coastal language and provide new insights into the phenomenon of ergative language in the local context. The implications of this research include supporting the development of linguistic studies and regional language studies and contributing to language teaching and translation in the region. Future research can be expanded to further investigate the features of ergative language in the Sibolga Coastal dialect and the context of its use in daily interactions.